1986
DOI: 10.1042/bj2360185
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Trypanosoma cruzi adenylate cyclase with liver regulatory factors

Abstract: Trypanosoma cruzi adenylate cyclase catalytic subunits may interact with regulatory factors from rat liver membranes, reconstituting heterologous systems which are catalytically active in assay mixtures containing MgATP. The systems show stimulatory responses to glucagon and guanosine 5'-[beta gamma-imido]triphosphate (p[NH]ppG) or fluoride. Reconstitution was obtained by three different methods: fusion of rat liver membranes (pretreated with N-ethylmaleimide) to T. cruzi membranes; interaction of detergent ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The purified catalytic subunit cross-reacts immunologically with enzymes from Neurospora and Mucor, but not with the vertebrate adenylate cyclase [53]. As noted above reconstitution of the Trypanosoma cyclase with regulatory factors from liver membranes confers sensitivity to guanine nucleotides [46], suggesting some fundamental homology between the trypanosomal and vertebrate enzymes. The soluble adenylate cyclase from Neurospora crassa could be activated by calmodulin, and EGTA reversed this activation [55].…”
Section: -S \~~~~~~~~~~~~~0mentioning
confidence: 80%
See 1 more Smart Citation
“…The purified catalytic subunit cross-reacts immunologically with enzymes from Neurospora and Mucor, but not with the vertebrate adenylate cyclase [53]. As noted above reconstitution of the Trypanosoma cyclase with regulatory factors from liver membranes confers sensitivity to guanine nucleotides [46], suggesting some fundamental homology between the trypanosomal and vertebrate enzymes. The soluble adenylate cyclase from Neurospora crassa could be activated by calmodulin, and EGTA reversed this activation [55].…”
Section: -S \~~~~~~~~~~~~~0mentioning
confidence: 80%
“…Further, antibodies against the 35 kDa fl-subunit of the guanine-nucleotide-binding protein reacted with a protein of that size from the abalone sperm. Eisenschlos et al [46] also showed that the Ca2+-dependent adenylate cyclase of Trypanosoma, although not itself sensitive to guanine nucleotides, came under the control of guanine nucleotides when reconstituted with regulatory proteins from liver. If the similarities between the Paramecium enzyme and the other Ca2+-sensitive cyclases extend to this property, one might predict the existence of guanine-nucleotide-binding proteins in Paramecium.…”
Section: -S \~~~~~~~~~~~~~0mentioning
confidence: 99%
“…Further studies on the interaction of photoreceptors and transducing proteins with plant membranes will improve understanding of the participation of plant G-proteins in the lighttransduction pathway. With animal tissues, cell-free reconstituted systems containing receptors, transducing proteins and effector entities (Flawiai et al, 1983;Eisenschlos et al, 1986;Muschietti et al, 1989), provided a better knowledge of the participation of G-proteins in lightor hormone-dependent transduction mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The regions responsible for the binding of the G sα and G βγ subunits of the heterotrimeric G‐proteins that regulate mammalian ACs are not conserved, suggesting that trypanosomal ACs are not regulated by G‐proteins homologous to those of mammals. Indeed, while some characteristics of G‐protein subunit activity have been reported in T. cruzi (Eisenschlos et al ., 1986; Coso et al ., 1992), no sequences homologous to the G‐protein subunits have been identified in the genomes of any of the kinetoplastids sequenced to date.…”
Section: Adenylyl Cyclases (Acs) Of Kinetoplastidsmentioning
confidence: 96%